ANALYSIS OF UNCERTAINTY DURING THE COVID-19 PANDEMIC ON NIM, ROA, NPL, AND BOPO AT RURAL BANKS - Ida Bagus Putu Siwa Adnyana; Irene Rini Demi Pangestuti (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This study analyzes the effect of uncertainty due to the Covid-19 pandemic on the financial performance of conventional BPRs in Bali during the period 2016-2023. This research is important because it can provide insight into how strong BPR banks are in facing the crisis. Analysis of NIM, ROA, NPL, and BOPO, can understand the bank's ability to maintain profitability and operational efficiency amid economic uncertainty. Uncertainty is measured through the standard deviation of assets, funding, and loan growth as independent variables, while financial performance is evaluated using the NIM, ROA, NPL, and BOPO ratios as dependent variables. The research method used is quantitative with multiple regression method, the research sample was 66 BPR in Bali and the data analysis technique used multiple regression with SPSS 27.00 software with four equations. The results of the study show that H1, H2, H3, H4, H10, and H11 do not meet the hypothesis, while H5, H6, H7, H8, H9, and H12 meet the hypothesis. In hypotheses H1, H2, H3 and H4, the independent variable, namely the standard deviation of assets, has a significant positive effect on the dependent variables NIM and ROA, and a negative effect on the dependent variables NPL and BOPO. Furthermore, in H10 and H11, the independent variable does not affect the dependent variable, which means that the standard deviation of loan growth does not affect ROA and NPL. In H5, H6, H7, H8, H9, and H12, the hypothesis shows that the standard deviation of funding has a significant negative effect on NIM and ROA, and a significant positive effect on NPL and BOPO. In addition, the standard deviation of loan growth has a significant negative effect on NIM and a significant positive effect on BOPO. Keywords: Uncertainty, Standard Deviation of Assets, Standard Deviation of Funding, Standard Deviation of Loan Growth, NIM, ROA, NPL, BOPO, BPR